Brentuximab vedotin in association with bendamustine in refractory or multiple relapsed Hodgkin lymphoma. A retrospective real‐world study. (13th March 2020) - Iannitto, Emilio; Romano, Alessandra; Scalzulli, Potito Rosario; Bonanno, Vincenza; Scalone, Renato; Chiarenza, Annalisa; Pirosa, Maria Cristina; Caruso, Anastasia Laura; Minoia, Carla; Mantuano, Saverio; De Santis, Gaetano; Salerno, Marilena; et al.
Abstract: Objective and Methods: In order to assess the efficacy of brentuximab vedotin (Bv) in combination with bendamustine (B) in multiple relapsed or refractory (RR) classic Hodgkin lymphoma (cHL), medical records of 47 patients treated with BvB in second relapse or beyond were reviewed. Results: The median number of previous treatments was 2 (1‐4). Bv was given at 1.8 mg/kg on day 1 and bendamustine at 90 mg/m 2 on days 1 and 2 of a 21‐day cycle. The median number of BvB cycles was 4 (2‐7), and all patients were evaluable for efficacy. The CR and OR rates were 49% and 79%, respectively; 67% of responding patients and 2 in stable disease proceeded to a SCT procedure. After a median follow‐up of 19 months (5‐47), median PFS was 18 months (95%CI: 23‐29), and the 2‐year OS was 72%. Significantly longer PFS and OS were observed in patients attaining a major clinical response to treatment and in those who received consolidation with SCT. Fifteen (32%) patients experienced severe (G > 2) toxicity. The main toxicities were neutropenia (23%), gastrointestinal (10%), peripheral sensory neuropathy (11%), and infection (4%). Conclusion: Our real‐world results suggest that BvB is an effective third‐line rescue and bridge‐to‐transplant regimen for RR‐cHL patients.